Long-run effects of technological change: The impact of automation and robots on intergenerational mobility - Fredrik Heyman; Martin Olsson (Research Institute of Industrial Economics (IFN), 2023)
This paper examines whether recent advancements in automation and robotics have affected intergenerational income mobility. Using detailed data on all individuals and firms registered in Sweden, we study whether parental exposure to robots at the occupational level and heterogeneous adoption of robots across industries and regions influence children's outcomes in adulthood. We find that occupational exposure to robots is associated with lower income mobility for children. Based on a shift-share IV approach, we show that the lower intergenerational income mobility originates from industry-regions with a relatively large increase in robot adoption. In addition, we show that these children are worse off on a number of labor market and family-related outcomes. Our results point to a new channel through which technological changes affect intergenerational mobility and indicate that automation and exposure to new technologies can have long-lasting effects.
Keywords: J24; J31; J62; O33; 330; Intergenerational Mobility; Automation; Robots; Matched Employer-Employee Data